Simulation analysis and calculation of aircraft tire hydroplaning based on SPH method - XIAO Liuwei; LIU Bin; XU Fei; FENG Wei; SONG Jinhui; QI Xuliang; MAO Congcong (Hangkong gongcheng jinzhan, 2023)
Aircraft tire hydroplaning can cause a sharp decrease in friction between it and the ground, increasing the takeoff and landing distance of the aircraft, and thus affecting flight safety. Therefore, it is necessary to carry out research on airplane tire hydroplaning. Aiming at the tire hydroplaning problem of aircraft tires, a simplified tire model was established by FEM method and verified by experiments. A water model was established by SPH method,and finally a tire hydroplaning model with the interaction of tire, water and pavement was established. The influence of different influencing factors and different tire configurations on tire hydroplaning was analyzed. The results show that, the greater the water depth, the more likely occur the tire hydroplaning, but after the water depth is greater than 6 mm, the water depth on the tire hydroplaning effect is small; The greater the tire speed, tire pressure and wheel load, the more likely the tire hydroplaning; With the increase of groove width, the tire hydroplaning speed increases, but the stability decreases. The more severe the tire abrasion, the more likely it is to tire hydroplaning; The greater the number of grooves, the greater the critical water skiing speed.